Implementation of Humanistic Learning Theory in Islamic Religious Education Learning - Suroso PR; Ani Aryati; Titin Yenni; Septiana Putri; Eka Yanuarti; Ahmal Ahmal (STAI Hubbulwathan Duri, 2023)
This study aims to find out how the application of humanistic learning theory in learning Islamic religious education in one of the State Middle Schools in Ogan Ilir Regency. The method used in this research is descriptive qualitative. The research instruments used were observation, interviews and documentation. Researchers used the snowball sampling technique or snowballs. To increase the validity of qualitative research data, a process of credibility, transferability, dependability, and confirmability is carried out. The results of this study indicate that students can maximise their potential or abilities by applying humanistic learning theory in Islamic religious education. For this reason, humanistic education is essential: each student has their own unique personality and skill set, and it would be unfair to expect each student to learn in the same way. The implementation of this humanistic theory has been successful. This is evident in the kids' daily life, as they worship in congregations with order, respect their elders, memorise large portions of the Al-Qur'an, and have warm, friendly relationships with their teachers. Teachers help pupils learn and develop strategies for overcoming challenges.